Application of the Bayesian networks in construction engineering - Leśniak, Agnieszka; Janowiec, Filip (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Currently, significant development of methods supporting decision making under uncertainty conditions is observed. One of such methods includes Bayesian networks used in many fields of economy and science. The paper presents the use of the Bayesian network method in civil engineering problems with particular emphasis on construction engineering projects. In addition to the existing examples of the use of the method cited, the authors? method for the risk estimation of additional works is presented.
Keywords: Bayesian networks; construction engineering; risk management; sieci bayesowskie; inżynieria budowlana; zarządzanie ryzykiem